Inhibition of Biofilm Formation in Agrobacterium tumefaciens by Cell-Free Supernatants of Pseudomonas aeruginosa Analyzed by GC-MS (Baghdad Science Journal, 2024)
One of the most economically significant plant pathogenic bacteria is Agrobacterium tumefaciens, infects plants by exploiting biofilms it forms on their surfaces wounds. This article has been concerned with the need for new antibacterial agents due to the limitations of current treatments. The capacity of Pseudomonas aeruginosa cell-free supernatant to inhibit the A. tumefaciens-produced biofilms as well as its chemical makeup were examined in this work. Using the API 20E kit and polymerase chain reaction of the 16S rRNA gene, P. aeruginosa was isolated from the soil and identified. It displayed a 93% identity with the common bacterium Pseudomonas sp.SeaQual P_B_845W, MT626817.1 in the GenBank. Using the microdilution method, the ability of the lyophilized supernatant was then determined at nine concentrations (10, 15, 20, 25, 30, 35, 40, 45, and 50%) of biofilm formation. The results revealed an inhibitory effect as percentages of 66, 61, 51, 27, 20, 17, and 15%,. After being injected with the GC-MC device, it was found that it consisted of 30 chemical compounds, which were identified by their names as;(Pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-, Hexadecanoic acid, methyl ester, Pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methyl propyl)-, 9-Octadecenoic acid (Z)-, methyl ester, and cis-13-Octadecenoic acid, methyl ester, Octadecanoic acid, methyl ester), this demonstrates that its (154, 270, 210, 296, 296, 298) Daltons and (9.38, 19.12, 6.8, 4.45, 8.33, 5.90)% of the total space. The discovery that P. aeruginosa cell-free supernatants include chemical compounds for the first time and have an inhibitory influence to produce biofilms by A. tumefaciens is the study's most significant finding.